Death and transcendence in northern European art - Pratt, S R (Rhodes University, Faculty of Humanities, Department of Fine Art, 1977)
[From Introduction]. Time has revealed two distinct tendencies in the history of thought and art in Europe. That development in European culture which began in Ancient Greece is marked by a positive confidence in the relationship of man to his world. Parallel with but in opposition to this development is a separate progression in culture. The continuity of art in Northern Europe appears to be associated with the adherence of Northern man to a negative, fatalistic sense of being - to a spirit which is in conflict with a hostile violent environment. The purposo of this investigation is to determine, through art the nature of this sense of being in Northern Europe. No direct definition would be capable of conveying the fullest meaning of that spirit. lt is a feeling. To understand this morbid fatalism, it is therefore necessary to refer to the pre-Christian religion of the Germanic Barbarians - through which the Northern spirit manifested itself in the form of ragnarök. Ragnarök which can be translated as a moaning obscurity, shadows, twilight, fateful destiny, was a term used by Nordic bards in its broadest sense to describe the end of the world - the inevitable destruction of life.
Keywords: Death in art; Art -- Europe, Northern